Construction of a unique anti-corrosion nanocomposite based on graphene oxide@Zn3PO4/epoxy; experimental characterization and detailed-theoretical quantum mechanics (QM) investigations. (30th September 2020) - Asaldoust, Sina; Hosseini, Mahdi Salami; Ramezanzadeh, Bahram; Bahlakeh, Ghasem
Graphical abstract: Highlights: A smart self-healing nanocomposite coating with promising active/barrier functions was designed. Zinc phosphate (ZP) decorated graphene oxide was obtained through one and two-steps in-situ methods. The effectiveness of 0.15 wt% GO-ZP composite in epoxy coating active inhibitive/barrier performance promotion was shown. The theoretical density functional theory (DFT) results declared the zinc phosphate adsorption on the GO surfaces. Abstract: The highly crystalline zinc phosphate (ZnP) compounds were synthesized over the graphene oxide surface through one and two-steps in-situ methods (namely GO-ZnP I and II). FT-IR studies revealed that the CO peak weakened or completely removed in the GO-ZnP I, II samples. Raman spectroscopy results evidenced the higher ID /IG ratio for the unmodified GO than GO-ZnP I and II, confirming the zinc phosphate crystals growth on the GO surface. Results of XPS and Raman spectroscopy proved the GO-ZnP I and II crystals formation on the GO platelets. ICP analysis results depicted about 11.6 ppm and 10.7 ppm zinc ions presence in NaCl solution, evidencing the partial solubility of the GO-ZnP I and for GO-ZnP II particles. A smart self-healing nanocomposite coating with promising anti-corrosion effect and dual active/barrier functions was designed using GO-ZnP I and II nanosheets. EIS studies on mild steel samples exposed to the saline solutions containing GO-ZnP I and GO-ZnP II particles extract demonstrated inhibition efficiencies of about 76 and 69%, respectively. According to EIS analysis, the total resistance ( R t ) values of 11480, 12048, 9105, and 7512 Ω·cm 2 were recorded for the EP/GO-ZPII, EP/GO-ZPI, neat epoxy, and EP/GO samples, respectively, after 48 h of exposure to saline solution confirming the superior anti-corrosion performance of the scratched EP in the presence of GO-ZP particles. The GO-ZPII loaded epoxy matrix showed low-frequency impedance values greater than 10 10 Ω·cm 2 even after 39 days of exposure, indicating the superior barrier effect of the particles in the coating formulation. The EIS evaluation and accelerated salt-fog spray corrosion test results showed the effectiveness of GO-ZnP II and I composites (at 0.15 wt% loading) in epoxy coating active inhibitive/barrier performance promotion. Additionally, the theoretical density functional theory (DFT) results declared the zinc phosphate adsorption on the GO surfaces.